The Emancipation of Household Accounting: A [Non]-Feminist Critical Study of Tjoet Njak Dien - Ramadhani, Febrina Nur; Purwanti, Lilik; Mulawarman, Aji Dedi (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study explores household accounting practices in the families of women migrant workers from a gender perspective, highlighting shifts in the traditional roles of Muslim women. The researcher employs a critical approach using the female nationalist heroine Tjoet Njak Dien as a central figure, utilizing a non-feminist theoretical framework to achieve the study’s objectives. The findings reveal that household accounting practices among migrant workers are characterized by a predominantly masculine orientation. Drawing on the metaphor of Tjoet Njak Dien’s continued struggle, the study identifies three strategies for effective household accounting. The first strategy emphasizes earning income in alignment with the principles of halal and toyyib, prioritizing ethical considerations and tangible benefits. The second strategy involves managing household finances with a balanced and deliberate approach. Finally, the third strategy highlights the importance of transparent communication and mutual understanding between husband and wife in financial decision-making. Implementing these strategies could serve to balance the household financial management of female migrant workers, who often rely on a rational approach in their bookkeeping practices. Keywords :   feminism, gender, household accounting